The Empathic Communication Analytical Framework (ECAF): A multimodal perspective on emotional communication in interpreter-mediated consultations - Theys, Laura; Nuyts, Lise; Pype, Peter; Pype, Willem; Wermuth, Cornelia; Krystallidou, Demi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Empathic communication (EC) in healthcare occurs when patients express empathic opportunities, such as emotions, to which doctors respond empathically. This interactional process during which participants try to achieve specific communicative goals (e.g., seeking and displaying empathy) serves as a context in which doctors and patients perform verbal and nonverbal actions and collaboratively co-construct meaning. This applies to interpreter-mediated consultations (IMCs) too, where interpreters perform additional actions of a similar kind. However, there is a dearth of research on the ways in which participants perform these actions in the context of EC, and how these actions in turn help (re)shape the context of EC in IMCs (Theys et al., 2020). To date, any tools for studying EC investigate participants’ actions in isolation, without studying them in the context of EC or in relation to the participants’ awareness of their own and others’ ongoing interactions. In this article, we present the Empathic Communication Analytical Framework (ECAF). The tool draws on valid, complementary analytical tools that allow for a fine-grained, three-level multimodal analysis of interactions. The first level of analysis allows for instances of EC in spoken language IMCs to be identified and for participants’ verbal actions in the context of EC to be studied. The second level allows analysts to investigate participants’ verbal and nonverbal actions in the previously identified context of EC. The third level of analysis links the participants’ concurrent verbal and nonverbal (inter)actions to their levels of attention and awareness and shows how participants’ actions are shaped and in turn help to reshape the context of EC in IMCs. In this article, we present the various levels of the ECAF framework, discuss its application to real-life data, and adopt a critical stance towards its affordances and limitations by looking into one excerpt of EC in IMCs. It is shown that the three distinct yet interconnected levels of analysis in the ECAF framework allow participants’ concurrent multimodal interactions in the context of EC to be studied.